foot and mouth disease in some areas of Nainawa province during may 2007 - Hussein, Zaid Salah (The Iraqi Journal of Veterinary Medicine, 2008)
For the determination of FMD infection in Nainawa province Serumsamples were collected from 92 suspected cases (42sheep,50cattle)thiswas performed in September 2007 and included nine region(Talafar,Basheca, Al-shamal, Hamamalaleel ,Cokajlly ,Zamaar ,Al-Namrood,AL-Koosh and Hemedaat), these samples were send frozen to the labs ofstate Vet. Company in Al-Nahdaa , the special test FMD-3ABC bo Ovenzyme immune assay on sheep serums showed that 30.95% werepositive to the test and 19.05% were ambiguous while the test on bovineserums showed increase in both positive and ambiguous results(42%,26% respectively), 8 serums that showed the highest positive resultto the former test were submitted to the special immunological test FMDElisa Kit Liquid Phase Blocking Immunoassay for detection of antibodiesof foot and mouth disease virus test which revealed that all sores of thesamples were infected with O serotype FMD